‘Lost Space’ Found: Reconsidering Functional Ambiguity as a Strategy for Housing Design - Dias, Tiago Lopes; Ramos, Rui Jorge Garcia; Lameira, Gisela (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The current response to housing issues, undoubtedly a pressing problem of our time, implies an acceptance of the diversity of ways of living and their transformation over time, in addition to factors such as demographic movements, the ageing of the Western population, and climate change, which call for a thorough review of housing types and their implementation. A review of this calibre cannot be conducted without the awareness that the problem, despite its current nature, has persisted over time, and given rise to an extensive body of knowledge. This paper aims to highlight the innovative design strategies geared towards a more open configuration of the dwelling and which are supported by theoretical research. The text opens by revisiting the free plan in its multiple configurations as the seed of adaptable design and advances to offer a more in-depth examination of the case of Portugal in the 1960s, a period in which the construction of affordable housing underwent considerable development. The notions of lost space, superfluous space, circulation and functional ambiguity emerge in this context of scarcity with great critical acuity. A short selection of contemporary case-studies, included in the last section of the paper, lead to a renewed reflection on the pertinence and relevance of these notions applied to current housing design.